PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTUAN MULTIMEDIA INTERAKTIF BERBASIS TPACK TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X SMAN 9 SAMARINDA - Andriani, Selvi; Rambitan, Vandalita MM; Tindangen, Makrina; Herliani, Herliani (BIOEDUKASI (Jurnal Pendidikan Biologi), 2025)
This study investigates the academic performance of Grade X science students at SMA Negeri 9 Samarinda through the implementation of a Project-Based Learning (PjBL) model integrated with TPACK-based interactive multimedia. A quantitative descriptive approach with a quasi-experimental design was employed. The research was conducted at SMA Negeri 9 Samarinda, a newly established school located on Jl. Lempake, which began operations in March 2024. Both experimental and control groups were administered a pretest prior to the learning intervention. The experimental group recorded a mean pretest score of 31.33 (on a scale of 10 to 55), while the control group scored an average of 19.39, with scores ranging from 7 to 38. Posttest results showed that the experimental group achieved an average score of 81.36 (range: 70–92), whereas the control group averaged 68.48, with a maximum score of 90. The significant difference in posttest outcomes indicates that the TPACK-based PjBL model had a positive impact on students' academic achievement. The study concludes that the integration of interactive multimedia within a PjBL framework can enhance students’ understanding of environmental pollution and improve science learning outcomes at SMA Negeri 9 Samarinda.